ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM FASHION KOTA SURAKARTA (Jurnal Riset Manajemen dan Akuntansi, 2023)
The purpose of this study was to determine and analyze the effect of education level, business age, accounting knowledge, and accounting training on the use of accounting information in fashion SMEs in Surakarta. This research method uses quantitative methods. In this study, the data obtained was from distributing questionnaires to fashion SMEs in the city of Surakarta. The research sample collection method used the slovin method as many as 75 fashion MSME owners or managers in Surakarta City. The data used in this research is primary data. The analytical method was processed using the SPSS 25 software. The results showed that partially, education level and business age had a positive effect on the use of accounting information on fashion SMEs in Surakarta. The variables of accounting knowledge and accounting training have no effect on the use of information on fashion SMEs in the city of Surakarta.